Appropriated interiors - Schneiderman, Deborah, 1968-; Lasc, Anca I.; Tehve, Karin (Routledge, 2022)
"Appropriated Interiors uncovers the ways interiors participate explicitly and implicitly in embedded cultural and societal values and explores timely emergent scholarship in the fields of interior design history, theory and practice. What is "appropriate" and what is "inappropriate" now? These are terms with particular interest to the study of the interior. Featuring thirteen original curated essays, Appropriated Interiors explores the tensions between normative interiors that express the dominant cultural values of a society, and interiors that express new, changing, and even transgressive values. With case studies from the late-eighteenth century to the twenty-first century, these historians, theorists, and design practitioners investigate the implications of interior design as it relates to politics, gender, identity, spatial abstraction, cultural expression, racial expression, technology, and much more. An informative read for students and scholars of design history and theory, this collection considers the standards, assumptions, codes and/or conventions that need to be dismantled and how we can expand our understanding of the history, theory and practice of interior design to challenge the status quo"- Resumé vydavatel